Mongolia : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report, 2005)
This paper reviews Mongolia's Economic Growth Support Poverty Reduction Strategy (EGSPRS) Implementation Progress Report 2004. Mongolia's GDP grew by 5.6 percent in 2003, a fulfillment of the goal set out in the Main Guidelines for Economic and Social Development in 2003 to attain at least 5.2 percent economic growth. In 2003, the economy grew thanks to 1.4 percent increase in the agriculture sector, 0.8 percent in the industrial sector, and 3.4 percent in the service sector. The preliminary estimate for real economic growth in 2004 equals 10.6 percent.